Effects of spatial accessibility of community health services on the activities of daily living among older adults in China: a propensity score matching study - Li, Yuee; Liu, Xiaohui (Frontiers in Public Health, 2024)
The Chinese government proposes to establish a hierarchical diagnosis and treatment system, and attaches great importance to community health services.Under the background of population aging and the increase of older adults with disability, this study aimed to analyze the effect of spatial accessibility of community health services on the activities of daily living (ADL) among older adults in China.Methods: A research sample of 7922 older adults from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) data in 2018 was adopted. There were 2806 participants in the treatment group and 5116 participants in the control group. The propensity score matching method was adopted to match the treatment and control groups to calculate the values of average treatment effects on treated (ATT).The results of kernel density matching method showed that the factual ADL score of the treatment group was 10.912, the counterfactual ADL score of the control group was 10.694, and the ATT value was 0.218 (P<0.01). The spatial accessibility of community health services could significantly improve the activities of daily living among older adults in China. Meanwhile, there was urban-rural heterogeneity in the impact of spatial accessibility of community health services on the activities of daily living of older adults in China. The effect value in urban samples (ATT=0.371, P<0.01) was higher than that in rural samples (ATT=0.180, P<0.01).Spatial accessibility of community health services could improve the activities of daily living among older adults in China. The Chinese government should take actions to improve the distribution of community health service resources.